2018
DOI: 10.1111/tbj.13052
|View full text |Cite
|
Sign up to set email alerts
|

Management of intraductal papilloma without atypia of the breast diagnosed on core biopsy: Size and sampling matter

Abstract: Due to the potential for atypia (atypical ductal or lobular hyperplasia) or carcinoma (in situ or invasive) on excision, aggressive reflex surgical excision protocols following core biopsy diagnosis of papillary lesions of the breast (ie, intraductal papilloma) are commonplace. Concepts in risk stratification, including radiologic-pathologic correlation, are emerging in an effort to curb unnecessary surgeries. To this end, we examined all excised intraductal papillomas diagnosed at our institution from 2010-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In a separate investigation involving 520 cases, a lesion size of 1.5 cm on imaging was identified as an independent predictor of malignancy [15]. Another study indicated an increased likelihood of atypia when the lesion size exceeded 1.2 cm [16]. Jaffer et al [17] reported no instances of upgrade in 46 patients diagnosed with IDP lesions smaller than 2 mm.…”
Section: Discussionmentioning
confidence: 97%
“…In a separate investigation involving 520 cases, a lesion size of 1.5 cm on imaging was identified as an independent predictor of malignancy [15]. Another study indicated an increased likelihood of atypia when the lesion size exceeded 1.2 cm [16]. Jaffer et al [17] reported no instances of upgrade in 46 patients diagnosed with IDP lesions smaller than 2 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 234 patients diagnosed with IDP without atypia, upgrade-related factors were age (>54 years) and mass size (>1 cm). Recent studies also proposed lesion size from >1 cm to >1.5 cm as a potential predictive factor [13,14,29]. Other factors such as prior breast atypia or cancer history, palpability, peripheral location and radiological-pathological discordance have also been evaluated, but discrepancy among study results has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies advocated immediate excision due to the significant upgrade rate to cancer from benign IDP after surgery or during follow-up [6][7][8][9][10][11][12]. In recent studies, close surveillance rather than surgery may be considered in the subgroup of patients, with small lesion size [13,14], non-palpability [15], radiological-pathological concordance [14,15], or no personal history of breast cancer [16]. The rationale for close observation in patients with CNB-confirmed IDP is the low upgrade rate to malignancy at the time of surgery [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Second, 277 benign papillary lesions (218 from the US-guided DVAR group and 59 from the US follow-up without intervention group) underwent imaging follow-up rather than surgical excision. As previously reported, complete removal of all imaging evidence of a breast lesion by using the available percutaneous biopsy methods does not ensure complete excision, even if there is no evidence of a upgrade (8,10,25). The American Society of Breast Surgeons guidelines recommend that the decision to excise should be individualized according to risk, such as size of lesion, symptoms, and risk of breast cancer (26).…”
Section: Discussionmentioning
confidence: 99%